The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/ol.2018.7861
|View full text |Cite
|
Sign up to set email alerts
|

miR-106b promotes cell invasion and metastasis via PTEN mediated EMT in ESCC

Abstract: Abstract. MicroRNA (miR)-106b serves an essential function in a variety of human cancer types, particularly in the process of invasion and metastasis. However, the function and mechanism of miR-106b in the invasion and metastasis of esophageal squamous cell carcinoma (ESCC) has remained elusive. In the present study, it was demonstrated that miR-106b was upregulated in ESCC tissues and cell lines. Furthermore, miR-106b expression in ESCC tissues was positively associated with lymphatic metastasis. Inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Third, mechanically, our previous study demonstrated that miR‐106b determines the effect of transforming growth factor β, a key EMT inducer, on the tumor behavior of breast cancer cells by targeting RB . Several studies have also demonstrated that a variety of genes were identified as the target of miR‐106b including caspase‐7 , PTEN , and Smad7 , which contribute to miR‐106b‐mediated EMT of cancer cells. In this scenario, CTC‐specific miR‐106b plays a critical role in regulating the EMT of CTCs, indicating that CTCs with higher expression of vimentin and miR‐106b show a higher motility in the bloodstream and more easily interact with the intravascular microenvironment, extravagate through the microvasculature, and interact with the metastatic microenvironment of target organs.…”
Section: Discussionmentioning
confidence: 94%
“…Third, mechanically, our previous study demonstrated that miR‐106b determines the effect of transforming growth factor β, a key EMT inducer, on the tumor behavior of breast cancer cells by targeting RB . Several studies have also demonstrated that a variety of genes were identified as the target of miR‐106b including caspase‐7 , PTEN , and Smad7 , which contribute to miR‐106b‐mediated EMT of cancer cells. In this scenario, CTC‐specific miR‐106b plays a critical role in regulating the EMT of CTCs, indicating that CTCs with higher expression of vimentin and miR‐106b show a higher motility in the bloodstream and more easily interact with the intravascular microenvironment, extravagate through the microvasculature, and interact with the metastatic microenvironment of target organs.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the cells undergoing EMT also exhibit down-regulation of epithelial markers (e.g., E-cadherin, ZO-1, claudins, and cytokeratins) and up-regulation of mesenchymal markers (e.g., vimentin, fibronectin, and a-smooth muscle actin) (40,41). Interestingly, EMT is a preceding event of invasion and metastasis cascades of cancers (39,42). The correlation between EMT and survival has been recently reported in RCC patients (43).…”
Section: Discussionmentioning
confidence: 99%
“…The major reason for most cancer deaths is tumor metastasis, which is possibly due to both reorganization of cancer cells’ gene expression and altered differentiation that lead to the epithelial-to-mesenchymal transition (EMT) ( Ding, 2013 ; Bill and Christofori, 2015 ; Reiter et al, 2017a ; Zhang et al, 2018 ). Altered cell-to-cell linkage permits the separation of neoplastic cells from the primary tumor and then the modifications of the extracellular matrix allow tumor cells to penetrate the surrounding stroma to reach the blood vessels, thereby generating metastasis ( Cavallaro and Christofori, 2001 ; Langley and Fidler, 2011 ; Zheng et al, 2016 ).…”
Section: Melatoninmentioning
confidence: 99%